2009
DOI: 10.1007/s10916-009-9349-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flow–Volume Spirometric Test Using Neural Network Based Prediction and Principal Component Analysis

Abstract: In this work, an attempt has been made to enhance the diagnostic relevance of spirometric pulmonary function test using neural networks and Principal Component Analysis (PCA). For this study, flow-volume curves (N = 175) using spirometers were generated under standard recording protocol. A method based on neural network is used to predict the most significant parameter, FEV(1). Further, PCA is used to analyze the interdependency of the parameters in the measured and predicted datasets. Results show that the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, we found that this methodology outperformed more advanced regression regularization techniques in reducing the bias and the dispersion of the residuals. Nowadays, in an era of exploding computational capabilities, neural networks represent the backbone of many emerging artificial intelligence techniques, which could successfully be applied in our field [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that this methodology outperformed more advanced regression regularization techniques in reducing the bias and the dispersion of the residuals. Nowadays, in an era of exploding computational capabilities, neural networks represent the backbone of many emerging artificial intelligence techniques, which could successfully be applied in our field [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the developed classifiers was estimated using False Positive (FP), False Negative (FN), True Positive (TP) and True Negative (TN) values [10]. Classification of a normal data as abnormal is considered as FP and classification of abnormal data as normal is considered FN.…”
Section: Performance Analysismentioning
confidence: 99%
“…PCA is a statistical method used to transform the input space into a new lower dimensional space. PCA technique has been investigated before by researchers for signal and image processing [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation